Unveiling the Dynamics of Public Policy Research: Productivity, International Collaboration, and Thematic Evolution - Utama, Dedy Kusna; Rusli , Budiman; Karlina, Nina; Sukarno, Dedi (Journal of Posthumanism, 2025)
This study aims to measure the academic contribution of journals based on productivity and citation influence, map patterns of scientific collaboration between countries, and cluster general themes and topics of public policy and policy analysis research from the past decade. Using the Scopus database, 278 articles were found, which were then analysed using the bibliometric analysis method with the Biblioshiny and VOSviewer analysis tools. The results show that the Policy Sciences journal dominates the domain of research development on public policy as the most influential source regarding the number of publications and citation quality, followed by Policy and Politics. Regarding country contributions, the United Kingdom is in the top position with the highest academic impact, followed by the USA and the Netherlands, which, although different in contribution volume, still show an important role in the global research landscape. Western Europe generally shows a higher level of international collaboration than other regions. Thematic contributions become a growing discourse for theme clustering, where research development direction indicates three main trends: consolidation and deepening of core issues, strengthening theoretical approaches, and responding to global dynamics such as crises and geopolitical changes. In addition, five general themes have been successfully clustered as a framework for understanding the direction of public policy and policy analysis research to date, which can be a reference for designing further research.